Software engineering research, management and applications - Lee, Roger (Studies in Computational Intelligence, 2014)
The purpose of the 11th International Conference on Software Engineering Research, Management and Applications (SERA 2013) held on August 7 - 9, 2012 in Prague, Czech Republic was to bring together scientists, engineers, computer users, and students to share their experiences and exchange new ideas and research results about all aspects (theory, applications and tools) of Software Engineering Research, Management and Applications, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them.   The conference organizers selected 17 outstanding papers from those papers accepted for presentation at the conference in order to publish them in this volume.  The papers were chosen based on review scores submitted by members of the program committee, and further rigorous rounds of review.